O przekładzie dygresji i intertekstu na tle „wyrw nieenroicznych” - Bednarczyk, Anna (Przekłady Literatur Słowiańskich, 2024)
The author examines the reconstruction of digressions and intertextual references comparing the poem Polish Flowers by Julian Tuwim and its Russian translation. She draws attention to numerous “gaps” — omissions visible in the translation. She notes that they are the opposite of “enroic gaps” (the term coined by Henryk Lebiedziński), which made it possible to guess the omitted content (message). Hence, she introduces the term “non-enroic gaps”. As a result, she comes to the conclusion that the digressiveness of the Polish work has been lost in the translation, for which these “gaps” are to blame.